A Review on Vocational Education in India - M. Devendra (AG Volumes, 2022)
Vocational education is a kind of training aimed at preparing students for work in the manufacturing or commercial sectors. It is possible to get it in a formal setting, such as at a trade school or a technical secondary school; in an informal setting, such as by picking up the essential skills on the job; or in all of these settings, simultaneously. Students who want to gain new skills and get a job quickly may find vocational education to be an excellent option. These programmes include an extremely wide range of subjects and may train you to become an expert in a variety of specialised fields, such as graphic design or welding. Learning about these educational alternatives will help you identify and pursue a vocational employment that corresponds with your professional goals and endeavours. Vocational education and developing skills are crucial to increase the efficiency and productivity of employees consequently leads to growth of national development. India is undergoing a shift toward a knowledge-based society, which necessitates a concerted effort to improve the country's human capital. A highly trained labour force is an essential need for achieving fast economic development, high levels of productivity, and a decrease in unemployment. Education in the arts and sciences, including vocational and technical training, is seen as an essential component of a country's economic growth.